A spectroscopic study of benzonitrile. (June 2022) - Rajasekhar, B.N.; Dharmarpu, Vijay; Das, Asim Kumar; Shastri, Aparna; Veeraiah, A.; Krishnakumar, Sunanda
Highlights: First report of absorption cross-sections of benzonitrile in the UV-VUV(4.5–11 eV). Spectral analysis & assignment of valence, Rydberg & charge transfer transitions. Revisit of IR spectrum & assignment of fundamental modes aided by NBO analysis. Quantum chemical calculations using DFT & TDDFT methods to support the analysis. PEC calculations help identify proposed hidden state as the valence state 1A2(1A"). Abstract: A spectroscopic study on benzonitrile has been carried out by recording photoabsorption spectra in the 36, 000–90, 000 cm −1 (4.5–11 eV) region using the synchrotron light source Indus 1 and infrared spectra in the 500–4000 cm −1 region using a Fourier transform infrared spectrometer. The observed electronic spectrum encompasses rich vibrational spectra corresponding to the π→π* valence transition in the 36, 000–62, 000 cm −1 region. Further, the 62000–90000 cm −1 region predominantly comprises of weak Rydberg transitions of the ns and np type riding on a broad continuum. Vertical excited states calculated using the TDDFT methodology give new insights into the interpretation of the valence and Rydberg transitions by corelating them with the observed spectral peaks and shifted benzene transitions. Excited electronic states of benzonitrile are classified as local excitations and /or charge transfer excitations from the percentage contributions predicted with the aid of quantum chemical calculations. A reinvestigation of the titled compound with quantum chemical calculations using DFT methodology predict the equilibrium geometry and ground state vibrational modes, while normal coordinate analysis establishes a good agreement with the observed molecular vibrations. Theoretically generated potential energy curves of low lying excited states provide additional insights into UV spectral features, photodissociation dynamics for formation of C5 H5 and CN radicals and could establish the identity of the hidden (dark) state postulated in an earlier work. For the first time, a comprehensive study of benzonitrile in the IR and UV-VUV regions is summarized in this paper.